2022
DOI: 10.3390/molecules27175622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Citri Reticulatae Pericarpium as an Anticancer Agent from the Perspective of Flavonoids: A Review

Abstract: Citri Reticulatae Pericarpium (CRP), also known as “chenpi”, is the most common qi-regulating drug in traditional Chinese medicine. It is often used to treat cough and indigestion, but in recent years, it has been found to have multi-faceted anti-cancer effects. This article reviews the pharmacology of CRP and the mechanism of the action of flavonoids, the key components of CRP, against cancers including breast cancer, lung cancer, prostate cancer, hepatic carcinoma, gastric cancer, colorectal cancer, esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Cancer originates from the clonal expansion and development of aberrant cells within the body [57]. With the changing prevalence and distribution of major risk factors, the global incidence and mortality rates of cancer are rapidly increasing [4]. Conventional cancer treatment methods include surgery, radiation therapy, chemotherapy, targeted therapy, hormone therapy, and immunotherapy [58].…”
Section: Anticancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer originates from the clonal expansion and development of aberrant cells within the body [57]. With the changing prevalence and distribution of major risk factors, the global incidence and mortality rates of cancer are rapidly increasing [4]. Conventional cancer treatment methods include surgery, radiation therapy, chemotherapy, targeted therapy, hormone therapy, and immunotherapy [58].…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Citri Reticulatae Pericarpium (CRP), commonly known as dried tangerine peel in English, is a widely used traditional Chinese medicine (TCM) derived from the mature peels of citrus plants belonging to the Rutaceae family, particularly various cultivated varieties of Citrus Reticulata [3]. Its use was first documented in "Shennong Ben Cao Jing", an ancient Chinese medicinal text, and has a history spanning thousands of years in China [4]. CRP is extensively utilized in TCM formulations and is also added as a flavoring agent in foods throughout China due to its distinct pharmacological properties, low toxicity, and high efficacy [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, issues in the research process continue to be a “stumbling obstacle” for NPs sought for application in the clinic. NPs including alkaloids, terpenoids, polyphenols, and anthraquinones regulate autophagy by influencing numerous signaling pathways including PI3K/AKT/mTOR, ERK, JNK, and AMPK [ 157 , 158 , 159 , 160 ]. On one hand, most studies on the mechanisms of NPs in the regulation of autophagy are still at an early stage.…”
Section: Limitationsmentioning
confidence: 99%
“…Ajitha et al (2012) isolated tricin from Njavara rice bran and found that radical scavenging activity increased exponentially with an increase in the O-H bond dissociation enthalpy (BDE), by 90.39 μg/mL of tricin. Subsequent studies have found that tricin has a strong ability to scavenge •OH radicals (Wang et al 2020) and has an inhibitory effect on cancer (Yu et al 2014;Song et al 2022). Although tricin is a strong free radical scavenger, the tricin content in lignin was not necessarily higher, resulting in lower median effective concentration (EC50) values for 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals (Xie et al 2021).…”
Section: Introductionmentioning
confidence: 99%